Journalism online - Ward, Mike (Oxford ; Boston : Focal Press, 2002)
Journalism Online tackles the pressing question of how to apply fundamental journalism skills to the online medium. It provides an essential guide to the Internet as a research and publishing tool. In particular, it examines how to forge key journalism skills with the distinctive qualities of the World Wide Web to provide compelling web content.Trainee and practicing online journalists will learn:- core journalism skills of identifying, collecting, selecting and presenting news and information;- multimedia skills such as audio recording and editing;- online research methods including use of se
1. What is online journalism -- Dot coms, dot bombs, dot rot and roll -- Some definitions -- What makes online journalism destinctive -- What has been the effect of all this on journalism so far -- Further reading and references -- 2. The core journalism -- 'You cannot teach journalism' -- The core journalistic process -- Further readding and references -- 3. Online research and reporting -- The impact of online on research and reporting -- Further reading and references -- 4. Writing -- Core writing skills -- Story structure -- Further reading and references -- 5. Online story construction -- Non-linear storytelling -- Writing for online -- Leverage those strengths -- Further reading and references -- 6. Who's afraid of HTML -- HTML : random definitions -- HTML : some urban myths -- Exercises -- Further reading and references -- 7. Design your web resource -- Conflicting views and common ground -- Language problems -- Is online the right medium for my message -- Who am I trying to communicate with -- Define the mission and goals for your site -- Consider and organize your potential content -- Putting the content sections into a structure -- Page inventories -- Give users the tools to find their way around the sections -- Present the whole package effectively -- Interface and usability -- Further reading and references
Includes bibliographical references and index
Keywords: Electronic journals; Electronic books